(3GdYedjGJ aj GdHfhc GdJLGQjI eY GdETGQI ddbQhV HGdJhbjY s - (3aVjdI (B, (3RhGhjs ((3GdLRGFQ(B:s (3OGQ CLjGd GdQbej (B,s, 2023)
(3jVe GdcJGH eGgjI GdHfhc GdJLGQjI, hXGFa GdHfhc GdJLGQjI hCfhGYgG, CgejI hCgOGa hejRGfjI GdHfhc GdJLGQjI ceG jVe GdbQhV GdHfcjI hGdbQhV HGdJhbjY hGdVeGf GdGMJjGWj HGdEVGaI Cfg jJMOK Yf GdcaGdI GdeUQajI hGdEYJeGO GdeSJfOj HCfhGYg BdjI SjQg eY PcQ efGaY GdGYJeGO GdeSJfOj, eNGWQg hGdGMJjGWGJ GdhGLH GJNGPgG bHd hHYO aJM GdGYJeGO(B.s
(3HjHdjhZQGajG(B: (3U U(B194-202s
Keywords: (3GdHfhc GdJLGQjIs; (3GdHfhc(B- (3GYJeGOGJs; (3GdbQhV GdeUQajIs